Pop-Up Book Learning Media Used with the Problem Based Learning Model to Determine Characters in Fictional Stories - Triani, Siti Hafida Nur; Nuryanto, Sukarir (Universitas Pendidikan Ganesha, 2024)
The low student learning outcomes in Indonesian are caused by a lack of media or a mismatch in the learning models used by teachers in learning. This research aims to develop Pop-Up Book learning media with a Problem-Based Learning (PBL) learning model to improve Indonesian language learning outcomes for fourth-grade elementary school students. This type of research is developed using the Borg & Gall development model. The research subjects were 25 students. The experts who are the subject of this research are media experts and material experts. The methods used to collect data are observation, interviews, questionnaires, documentation, and tests. This research instrument is in the form of a questionnaire and test questions. Data analysis techniques use data normality tests (Kolmogorov Smirnov), paired t-tests, and N-gain tests. The research results showed that after going through the product validation stage by material experts, a score of 90.9% was obtained. According to media experts obtained a score of 85.4% in the very feasible category. The effectiveness of the media was tested by calculating the results of the initial and final tests using the paired t-test. It was found that there were differences in the average learning outcomes before and after applying the Pop-Up Book learning media with the PBL model. It was concluded that the Pop-Up Book was effective and suitable for learning and improved students' ability to understand the material of finding fictional story characters in Indonesian subjects. The implication of this research is that the Pop-Up Book developed can be used in Indonesian language learning.